Peran Jaksa dalam Pengawasan Penyidikan Perkara Pidana - Putra, Bambang Sasmita Adi; Ridwan, Muannif (Indra Institute Research & Publication, 2026)
This study examines the role of prosecutors in supervising criminal investigations as an integral component of the Indonesian criminal justice system. The research aims to analyze the legal foundation of prosecutorial authority, the practical mechanisms of supervision, the challenges encountered in its implementation, and policy recommendations for strengthening oversight to ensure due process and protection of human rights. Using a qualitative approach with a document study design, the research analyzes primary legal materials, statutory provisions including Law No. 11 of 2021, and secondary sources such as academic literature and empirical studies. The findings show that prosecutorial supervision is normatively supported through pre-prosecution mechanisms, the issuance of investigative instructions, and institutional coordination between prosecutors and investigators. Effective supervision has been found to enhance the coherence of evidentiary construction and reduce procedural defects in case files. However, several obstacles persist, including institutional coordination gaps, high caseloads, limited resources, and inconsistent implementation of standard operating procedures. The study concludes that strengthening prosecutorial oversight is essential to improving the quality, accountability, and transparency of investigations. Clearer coordination mechanisms, adequate resources, and standardized guidelines are needed to ensure that prosecutorial supervision contributes effectively to safeguarding justice and human rights within the criminal process.